Les défenseurs des Indiens du Yucatán et l’accès des Mayas à la justice coloniale, 1540-1600 - Caroline Cunill (Nuevo mundo - Mundos Nuevos, 2011)
This study analyses the function of the Defensor de los Indios in Colonial Yucatan during the second half of 16th century. In spite of the regional concern, comparisons with the evolution of this office in other regions of America should not be discarded, in order to fully understand the Crown’s political orientations regarding matters of justice. We will try to find out the antecedents and the reasons alluded to in the political discourse that could lead to the creation of this new corps of Spanish monarchical functionaries. The defensores, sort of attorneys specialized in indigenous affairs, were supposed to enable Natives’ access to colonial legal system to be easier. In order to appraise the institution’s relative efficiency, it is also necessary to inquire about the Indian’s and specially the Mayas’ participation in the colonial justice system through the use they made of those functionaries, as well as the eventual benefits they managed to gain in defence of their own particular or collective interests.